Analysis of inequality in maternal and child health outcomes and mortality from 2000 to 2013 in China - Yanting Li; Yimin Zhang; Shuai Fang; Shanshan Liu; Xinyu Liu; Ming Li; Hong Liang; Hua Fu (BMC, 2017)
Abstract Background Inequality in maternal and child health seriously hinders the overall improvement of health, which is a concern in both the United Nations Sustainable Development Goals (SDGs) and Healthy China 2030. However, research on the equality of maternal and child health is scarce. This study longitudinally assessed the equality trends in China's maternal and child health outcomes from 2000 to 2013 based on place of residence and gender to improve the fairness of domestic maternal and child health. Methods Data on China's maternal and child health monitoring reports were collected from 2000 to 2013. Horizontal and vertical monitoring were performed on the following maternal and child health outcome indicators: incidence of birth defects (IBD), maternal mortality rate (MMR), under 5 mortality rate (U5MR) and neonatal mortality rate (NMR). The newly developed HD*Calc software by the World Health Organization (WHO) was employed as a tool for the health inequality assessment. The between group variance (BGV) and the Theil index (T) were used to measure disparity between different population groups, and the Slope index was used to analyse the BGV and T trends. Results The disparity in the MMR, U5MR and NMR for the different places of residence (urban and rural) improved over time. The BGV (Slope BGV = -32.24) and T (Slope T = -7.87) of MMR declined the fastest. The gender differences in the U5MR (Slope BGV = -0.06, Slope T = -0.21) and the NMR (Slope BGV = -0.01, Slope T = 0.23) were relatively stable, but the IBD disparity still showed an upward trend in both the place of residence and gender strata. A decline in urban-rural differences in the cause of maternal death was found for obstetric bleeding (Slope BGV = -14.61, Slope T = -20.84). Improvements were seen in the urban-rural disparity in premature birth and being underweight (PBU) in children under 5 years of age. Although diarrhoea and pneumonia decreased in the U5MR, no obvious gender-based trend in the causes of death was observed. Conclusion We found improvement in the disparity of maternal and child health outcomes in China. However, the improvements still do not meet the requirements proposed by the Healthy China 2030 strategy, particularly regarding the rise in the IBD levels and the decline in equality. This study suggests starting with maternal and child health services and focusing on the disparity in the causes of death in both the place of residence and gender strata. Placing an emphasis on health services may encourage the recovery of the premarital check and measures such as prenatal and postnatal examinations to improve equality.